Pain Management in Childbirth: A Global Perspective - Rejeki, Sri; Dhamanik, Reina (University of Muhammadiyah Semarang, 2023)
Childbirth pain is one of the most intense forms of pain that women experience, and its management is critical to both maternal and fetal well-being. Around the world, different methods of pain relief are used, ranging from non-pharmacological approaches to advanced medical interventions. This systematic review aims to examine the various pain management strategies employed globally, their effectiveness, and the disparities in access to these methods. It discusses both pharmacological and non-pharmacological approaches while highlighting the influence of cultural, healthcare, and infrastructural factors on pain management during labor.